Balance of Go1α and Go2α expression regulates motor function via the striatal dopaminergic system - Baron, Jens; Spanagel, Rainer (Journal of neurochemistry, 2018)
The heterotrimeric G-protein Go with its splice variants, Go1α and Go2α, seems to be involved in the regulation of motor function but isoform-specific effects are still unclear. We found that Go1α-/- knockouts performed worse on the rota-rod than Go2α-/- and wild-type (WT) mice. In Go1+2α-/- mice motor function was partially recovered. Furthermore, Go1+2α-/- mice showed an increased spontaneous motor activity. Compared to wild types or Go2α-/- mice, Go1+2α-/- mice developed increased behavioural sensitization following repetitive cocaine treatment, but failed to develop conditioned place preference. Analysis of dopamine concentration and expression of D1 and D2 receptors unravelled splice-variant-specific imbalances in the striatal dopaminergic system: In Go1α-/- mice dopamine concentration and vesicular monoamine uptake were increased compared to wild types. The expression of the D2 receptor was higher in Go1α-/- compared to wild type littermates, but unchanged in Go2α-/- mice. Deletion of both Go1α and Go2α re-established both dopamine and D2 receptor levels comparable to those in the wild-type. Cocaine treatment had no effect on the ratio of D1 receptor to D2 receptor in Go1+2α-/- mutants, but decreased this ratio in Go2α-/- mice. Finally, we observed that the deletion of Go1α led to a threefold higher striatal expression of Go2α. Taken together our data suggest that a balance in the expression of Go1α and Go2α sustains normal motor function. Deletion of either splice variant results in divergent behavioural and molecular alterations in the striatal dopaminergic system. Deletion of both splice variants partially restores the behavioural and molecular changes. Open Practices Open Science: This manuscript was awarded with the Open Materials Badge. For more information see: https://cos.io/our-services/open-science-badges/